2021
DOI: 10.3389/fchem.2021.783705
|View full text |Cite
|
Sign up to set email alerts
|

Terminal Cyclohexane-Type Meroterpenoids from the Fruiting Bodies of Ganoderma cochlear

Abstract: Eleven new cyclohexane-type meroterpenoids (1, 3–5, 7, 8, 11–15) and four known similar meroterpenoids (2, 6, 9, and 10) were isolated from Ganoderma cochlear. Their structures and absolute configurations at stereogenic centers were elucidated by using HRESIMS, NMR spectroscopy and computational methods. In addition, the structure of the known meroterpenoid, cochlearol G (2), was revised, and the absolute configurations at the stereogenic centers of known meroterpenoids 9 and 10 were determined. All the isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…Agents that interfere with the TGF-β 1 signalling pathway may provide anti-fibrotic benefit by inhibiting myofibroblast differentiation and collagen production [ 3 ]. This has been reported previously for small molecule meroterpenoids, petchiether A [ 24 ] and ganodercin M [ 25 ], isolated from the fruiting body of fungi, Ganoderma petchii and G. cochlear . The effect of Compound 1 on NFF-myofibroblast differentiation was examined by stimulating cells with TGF-β 1 (10 ng/mL) and immunostaining for α-SMA.…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…Agents that interfere with the TGF-β 1 signalling pathway may provide anti-fibrotic benefit by inhibiting myofibroblast differentiation and collagen production [ 3 ]. This has been reported previously for small molecule meroterpenoids, petchiether A [ 24 ] and ganodercin M [ 25 ], isolated from the fruiting body of fungi, Ganoderma petchii and G. cochlear . The effect of Compound 1 on NFF-myofibroblast differentiation was examined by stimulating cells with TGF-β 1 (10 ng/mL) and immunostaining for α-SMA.…”
Section: Resultssupporting
confidence: 72%
“…TGF-β 1 is known to induce NFF-myofibroblast differentiation via the activation of both Smad- and non–Smad dependent cell signalling pathways [ 28 , 29 ]. A recent study investigating the anti-fibrotic effects of the meroterpenoid, ganodercin M, found no effect on Smad2/3 phosphorylation in TGF-β 1 –stimulated rat renal proximal tubular cells (NRK-52E cells), suggesting a Smad-independent mechanism [ 25 ]. The precise mechanisms by which Compound 1 elicits its anti-fibrotic responses remain to be elucidated.…”
Section: Resultsmentioning
confidence: 99%
“…Given that the cyclohexane ring of compounds 42–45 (ref. 46 and 47) is present between C-6′ and C-11′, we deduce their possible biosynthetic pathways as follows: (1) the epoxidation of Δ 10′,11′ ; (2) C-6′ attacks C-11′ to form cation of C-7′; (3) deprotonation at C-6′, C-15′, and C-8′ respectively leads to the generation of derivatives 42–45 (Fig. 9).…”
Section: Structure and Hypothetical Biosynthesis Of Gmsmentioning
confidence: 99%
“…Similarly, since C-8′ is still an allylic position, thus, the six-membered carbon ring of compounds 48–55 (ref. 46) could be formed from fornicin D ( 13 ) by a series of free radical reactions, with allylic oxidation leading to the formation of the hydroxyls at C-8′ and C-9′ (Fig. 11).…”
Section: Structure and Hypothetical Biosynthesis Of Gmsmentioning
confidence: 99%
See 1 more Smart Citation